Design of cloud security in the EHR for Indian healthcare services - Pradeep Deshmukh (Journal of King Saud University: Computer and Information Sciences, 2017)
An ease of data or record sharing at will has compelled most of the physicians to adopt EHR (Electronic Health Record) for record-keeping of patients. It also makes convenient to the other stake holders of healthcare ecosystem such as nurses, specialists and patient. Due to lower costs and scalability of application, the cloud is becoming the infrastructure for most of the EHR but without comprising the privacy of data. In this paper we have proposed a frame work for storing the health records and accessing them by patients and physicians as authorized by key-control scheme. The scenarios we have considered here are of rural and urban health care centers and hence more appropriate for Indian health care services. The proposed scheme has double data security by introducing isolation between encryption schemes of transmitted data and stored data. The experimental result shows that it has a capability of scaling in number of patients and also no of elements in health record.